MATHEMATICAL THINKING SKILLS LEVEL AMONG INTERMEDIATE SCHOOL STUDENTS - Haya Mohammad H. Albaqawi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
The current study aims to reveal the level of the second intermediate grade students' possession of mathematical thinking skills. The descriptive approach was used to achieve the objectives of the study. A test that measures mathematical thinking skills was prepared and applied to 500 female students in public schools in the city of Hail, Saudi Arabia. The results of the study showed that the participants had a low level of mathematical thinking skills, which the order of which was as follows: the skill of visual-spatial perception, followed by the skill of symbolic expression, and finally the skill of logical thinking. The study recommended the necessity of spreading awareness of the importance of mathematical thinking skills in teaching mathematics, adopting educational programs that contribute to the development of mathematical thinking skills among female students, and highlighting the importance of including mathematical thinking skills in the curriculum for those in charge of preparing mathematics curricula.